TRAINING ON ENTREPRENEURSHIP PROPOSAL WRITING (PKM-K). - Faliza, Nur; Naz'aina, Naz'aina; Fahrizal, Effan (RADJA PUBLIKA, 2022)
This article aims to provide knowledge about entrepreneurship, especially those related to writing entrepreneurial proposals for PMK-K through training conducted on students. It is hoped that the proposals made by students are not only able to participate in PKM but are also sustainable. The method of delivering the training is the lecture and discussion method. Questionnaires were distributed after the training to the trainees, to see how far the participants understood the training material provided. After attending this training, students generally have knowledge about student creativity programs and their categories, in addition to entrepreneurship. Then students are able to find ideas and are also able to compile these ideas in the form of entrepreneurial proposals which are then collected.